2013
DOI: 10.1111/jels.12017
|View full text |Cite
|
Sign up to set email alerts
|

How Jurors Evaluate Fingerprint Evidence: The Relative Importance of Match Language, Method Information, and Error Acknowledgment

Abstract: Fingerprint examiners use a variety of terms and phrases to describe a finding of a match between a defendant's fingerprints and fingerprint impressions collected from a crime scene. Despite the importance and ubiquity of fingerprint evidence in criminal cases, no prior studies examine how jurors evaluate such evidence. We present two studies examining the impact of different match phrases, method descriptions, and statements about possible examiner error on the weight given to fingerprint identification evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 35 publications
7
59
0
Order By: Relevance
“…Finally, we examined general views on the reliability of fingerprint and DNA evidence. Consistent with prior research (Garrett & Mitchell, ), we found that the great majority of respondents believed that each individual's fingerprints are unique (1,222, or 84.3%) or are probably unique (189, or 13%), while only a few believed they that fingerprints are not individually unique (39, or 2.7%). A slightly smaller majority also believed that each individual's DNA is unique (1,188, or 81.9%) or is probably unique (173, or 11.9%), while a few believed an individual's DNA is not unique (89, or 6.1%).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Finally, we examined general views on the reliability of fingerprint and DNA evidence. Consistent with prior research (Garrett & Mitchell, ), we found that the great majority of respondents believed that each individual's fingerprints are unique (1,222, or 84.3%) or are probably unique (189, or 13%), while only a few believed they that fingerprints are not individually unique (39, or 2.7%). A slightly smaller majority also believed that each individual's DNA is unique (1,188, or 81.9%) or is probably unique (173, or 11.9%), while a few believed an individual's DNA is not unique (89, or 6.1%).…”
Section: Resultssupporting
confidence: 89%
“…In prior research, we found that a fingerprint examiner's admission that fingerprint identifications were sometimes erroneous and that his own identification opinion in the case at hand might be in error significantly reduced the weight given to fingerprint evidence in a criminal trial (Garrett & Mitchell, ). This result held whether the fingerprint expert raised the possibility of error during direct testimony or conceded that possibility on cross‐examination.…”
Section: The Problem Of Error In Forensicsmentioning
confidence: 90%
See 2 more Smart Citations
“…In prior research, we found that the particular categorical language used by fingerprint examiners mattered little: Categorical match opinions carried considerable weight regardless of whether the examiner stated that opinion starkly, bolstered it with unwarranted statements of certainty, or qualified it by admitting that someone other than the defendant might be the source of the latent prints . This prior research did not examine, however, whether the subjective probabilities of a match, as determined by an examiner, corresponded to the jurors’ assigned probabilities.…”
mentioning
confidence: 86%